2017
DOI: 10.1007/s10531-017-1334-8
|View full text |Cite
|
Sign up to set email alerts
|

A pan-neotropical analysis of hunting preferences

Abstract: Hunting in the neotropics is a widespread form of resource extraction. However, there is increasing concern that current activities are leading to the decline and extirpation of vulnerable species; particulary ateline primates, large ungulates (such as tapirs and white-lipped peccaries) and large birds such as curassows. Hunting patterns are expected to be a product of two principal influences: the value of return for a given amount of effort invested into hunting, and cultural factors that determine the prest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
3
14
1
Order By: Relevance
“…Unacknowledged or lost campesino LTK is a concern for campesino communities and conservation programs and denies conservationists insights into the targets and sustainability of campesino hunting. We found that campesinos hunt a wider diversity of species than documented in previous studies (Redford & Robinson 1987;Ojasti 2000;Stafford et al 2017). Campesinos mostly preferred mammals, birds, and reptiles of least conservation concern, a finding that is consistent with other hunting or human-wildlife conflict reviews in the Neotropics that included campesino populations (Table 1) (Torres et al 2018).…”
Section: Target Species and Hunting Sustainabilitysupporting
confidence: 87%
“…Unacknowledged or lost campesino LTK is a concern for campesino communities and conservation programs and denies conservationists insights into the targets and sustainability of campesino hunting. We found that campesinos hunt a wider diversity of species than documented in previous studies (Redford & Robinson 1987;Ojasti 2000;Stafford et al 2017). Campesinos mostly preferred mammals, birds, and reptiles of least conservation concern, a finding that is consistent with other hunting or human-wildlife conflict reviews in the Neotropics that included campesino populations (Table 1) (Torres et al 2018).…”
Section: Target Species and Hunting Sustainabilitysupporting
confidence: 87%
“…A variety of vertebrates are hunted or gathered in Central America and Amazonia (Alves and van Vliet 2018). A meta-analysis of 78 hunting studies, from sites located in Central America, Amazonia and the Guiana Shield, recorded a total of 90 hunted mammal species (Stafford et al 2017a), including 12 primate genera, 6 ungulate genera and 8 rodent genera. As in Africa, ungulates and rodents make up the majority of the wild meat offtake in neotropical communities.…”
Section: Chaptermentioning
confidence: 99%
“…Hunting is a major threat to several tropical mammalian and bird species worldwide (Benítez-Lopez et al 2017). Thousands of indigenous and traditional people in remote areas of Amazonia hunt several species for subsistence, some of which are key for ecosystem functioning (Redford & Robinson 1987, Doughty et al 2013, Stafford et al 2017). This subsistence hunting can impact local wildlife populations and communities, affecting the food security of forest families that rely on wildlife for meat.…”
Section: Introductionmentioning
confidence: 99%
“…Hunting norms are often part of such plans, and hunting with dogs is often regulated. Other indigenous and traditional people hunt with dogs using similar tactics and have regulated the use of dogs in their ILs or conservation units designated for the sustainable use of natural resources in the Brazilian Amazonia (Medeiros & Garcia 2006, Pezzuti & Chaves 2009, Figueiredo & Barros 2015) and elsewhere in the Neotropics (Koster 2009, Stafford et al 2017).…”
Section: Introductionmentioning
confidence: 99%